Papers - - Production - Domestic - Oil and Gas Development in Louisiana (e9100bcf-7cb3-4cc4-ba43-f8834faed63d) - Benjamin C. Craft (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1936)
Oil and gas development in Louisiana during 1935 brought this state at the close of the year up to fourth place in the nation as a producing area. A review of development in North Louisiana centers around Rodessa, the most important reserve discovered in this area in many years. While the producing limits have not been defined, this discovery is one of the major developments of the year. New gas fields were discovered in Lincoln, De Soto and Bossier parishes. The Lincoln Parish discovery, completed flowing a highly saturated gas from the Glen Rose, further indicates the importance of deep-seated prospects in the interior salt-dome area. Minor extensions were made at Sligo and Pine Island. During the year, 126 oil wells and 103 gas wells were completed in North Louisiana as compared with 144 oil wells and 68 gas wells during 1934. The North Louisiana oil production was 9,617,405 bbl. as com-pared with 9,274,050 bbl. during 1934, an increase of 343,355 bbl., while the gas production increased 18 billion cu. ft. in 1935 over its 1934 figure. The Louisiana Department of Conservation gage of Nov. 1, 1935, shows an open-flow capacity of 4,563,725,000 cu. ft. per day from 941 wells in the Monroe field and 682,770,000 cu. ft. from 159 wells in the Rich-land field. A great deal of leasing continues in North Louisiana as a result of the Lincoln Parish discovery and development in the Rodessa field, especially in Bossier, De Soto, Winn, Lincoln, Bienville, Webster, Ouachita and Richland parishes. South Louisiana's position as an area of important reserves was further proved during the past year. Increased drilling resulted in the discovery of seven new fields: Lafitte, Garden Island Bay, Tepetate, Bunkie, St. Martinsville, Jeanerette and Big Lake. New sands or producing horizons proved productive in 15 of the proven fields. The total oil production for South Louisiana during 1935 was 40,731,-056 bbl. as compared with 23,255,437 bbl. during 1934. There were 222 oil and gas wells completed in South Louisiana during 1935 as compared with 214 oil wells during the previous period. Drilling during